Brand identity co-creation dilemma - Alves, Antonio Pedro Cruz Costa (2023)
Purpose: Co-creation is a growing theme in the branding landscape, particularly regarding brand identity. Scholars argue that brands are no longer stable, permanent, or unilaterally defined but should be dynamic and co-created with several stakeholders. However, these two different views about brand identity reveal a dilemma: to co-create or not to create? Is brand identity at the same time constant and dynamic, enduring and ephemeral, created and co-created? Will co-creation help build strong brands or dilute them? This paper aims to address this apparent paradox and suggest theoretical propositions about the relationship between co-creation and brand identity.Methodology/Approach: We conducted a systematic review of articles about brand identity and co-creation. Through the literature analysis, we theoretically discuss the impact of co-creation on brand identity and relate it to the theories of social representations and central nucleus.Findings: We found that the co-creation process has several facets: the involvement of executives and internal employees, performances and negotiations among stakeholders, an evolutionary and potentially anarchic process of brand identity, and tensions and contestations.Theoretical Contribution: We formulated four proposals: (1) brand identity has a core, which is more enduring, and an extended identity, which is more malleable; (2) the closer co-creation gets to the core brand identity, the riskier it is to dilute it; (3) co-creation is a dynamic process that may negatively impact brand identity; and (4) the more the extended brand identity is co-created, the more brand equity is positively impacted.Originality: This study discusses the adverse outcomes of co-creation for brand identity, which scholars do not often evaluate. We also suggest a set of propositions about how far co-creation can be applied before it starts diluting brand identity.